MNGI-21. OPTIMISING PATIENT SELECTION FOR ANTIEPILEPTIC DRUG THERAPY IN MENINGIOMA SURGERY. (5th November 2018) - Islim, Abdurrahman; Ali, Arousa; Bagchi, Ananyo; Ahmad, Mohammad; Mills, Samantha; Chavredakis, Emmanuel; Brodbelt, Andrew; Jenkinson, Michael
Abstract: BACKGROUND: Epilepsy is a major cause of morbidity and mortality in meningioma patients. The aims of this study were to determine which factors predispose meningioma patients to developing perioperative seizures and to understand the impact of antiepileptic drugs. METHODS: Patients treated for a histologically-confirmed intracranial meningioma at the authors institution between 2010 and 2015 were retrospectively examined. Clinical and imaging data were assessed. Multivariate analysis was performed using binary logistic regression. The effect of antiepileptic treatment was assessed using survival analysis. RESULTS: Two hundred and eighty-three patients met the selection criteria; seizures were present in 68 (24%) preoperatively and in 48 patients (17%) following surgery. Of the 68 with preoperative seizures, 19 continued to have them, whereas de-novo seizures arose postoperatively in 29 seizure-naïve patients. Risk factors of postoperative seizures were convexity location (OR=2.05 [95% CI=1.07–3.98], p=0.030), fronto-parietal location (OR=4.42 [95% CI= 1.49–13.16], p=0.007) and preoperative seizures (OR=2.65 [95% CI=1.37–5.24], p=0.005). The two locations, in addition to the presence of midline shift on preoperative imaging (OR=4.15 [95% CI=1.54–11.24], p=0.005), were significantly correlated with postoperative seizures in seizure-naïve patients. Antiepileptic treatment in patients with those risk factors reduced the possibility of seizures at any time point within the 1st year postoperatively by approximately 40%, although this did not meet statistical significance. CONCLUSION: Prophylactic antiepileptic treatment might be warranted in seizure-naïve meningioma patients with 1 risk factor. High-quality randomised controlled trials are required to verify those factors and to define the role of antiepileptics in meningioma practice.